Handbook of research on social, cultural, and educational considerations of indigenous knowledge in developing countries - Ngulube, Patrick (Advances in knowledge acquisition, transfer, and management, 2017)
This book provides the latest scholarly research on the importance of knowledge and value systems at the community level and ways indigenous people utilize this information, highlighting impacts on culture and education in developing nations.